2009
DOI: 10.2478/s11536-008-0084-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum neopterin in workers exposed to inorganic dust containing free crystalline silicon dioxide

Abstract: AbstractThe study was conducted among 92 male workers, divided into two groups depending on workplace and level of inorganic dust containing free crystalline SiO2 in the work environment, and 43 healthy workers without exposure to dust aerosols. The measured inhalable and respirable dust concentrations, as well as the concentration of free crystalline silica (FCS) in the respirable fraction were different for the two groups, but the percentage of free crystalline silica in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
5
4
0
Order By: Relevance
“…Saito et al (29) used neopterin as a marker of activated alveolar macrophages in patients suffering from interstitial pulmonary diseases. In this paper, neopterin concentrations were increased not only in silicosis patients compared to controls, as in previous papers (28,30), but also in workers with a classifi ed progression of the pathology (Figure 1). Our results confi rm that silica exposure activates cellular immunity as well as that the progression of this immune reaction is positively correlated with the progression of disease severity as mentioned before.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Saito et al (29) used neopterin as a marker of activated alveolar macrophages in patients suffering from interstitial pulmonary diseases. In this paper, neopterin concentrations were increased not only in silicosis patients compared to controls, as in previous papers (28,30), but also in workers with a classifi ed progression of the pathology (Figure 1). Our results confi rm that silica exposure activates cellular immunity as well as that the progression of this immune reaction is positively correlated with the progression of disease severity as mentioned before.…”
Section: Discussionsupporting
confidence: 84%
“…Silica affects humoral and cellular immune responses and may have systemic effects while in the lungs and regional lymph nodes. Several lines of evidence support the view that the pathogenesis of silicosis involves uncontrolled immune processes (13,28). It is widely believed that the pathogenesis of fi brotic responses evoked by particulates involves the generation of macrophage-derived growth factor(s) that stimulate proliferation and collagen synthesis by fi broblastic cells in the lungs (15).…”
Section: Discussionmentioning
confidence: 96%
“…Such observations are consistent with findings that ascorbic acid prevents apoptosis by upregulating the Bcl-2 protein expression in various cell types [31] and also those of our recent report in rat thymocytes [32]. By detoxifying ROS, antioxidants may thereby reverse the ROS-induced decline in Bcl-2 and prevent cellular death [29,33,34,35].…”
Section: Discussionsupporting
confidence: 92%
“…Also there was a statistically significant negative correlation of Neopterin with the predicted percentage FEV1 (r=-0.45), FVC (r= -0.51) and FEV1/FVC (r= -0.41) (Table 3). These findings were in agreement with that of Prakova et al (2009) who found that serum Neopterin level was higher among coal mine workers who were exposed to free CS than controls and they concluded that exposure to free CS is associated with activation of cellular immunity and particularly macrophages.…”
Section: Discussionsupporting
confidence: 92%